struct {int x; char *y;}tab={1,"ab"},*p=tab; 则:表达式p->;x的结果为【1】。
1
举一反三
- struct { int x; char *y; }tab[2]={{1,"ab"},{2,"cd"}}, *p=tab;则表达式*p->;y的结果为____(1)___,表达式*(++p)->;y的结果为__(2)____。
- 有如下定义:struct {int x;char *y;}tab[2]={{1,"ab"},{2,"cd"}}, *p=tab;则:表达式 *p->;y的结果是( ① ) 。表达式 *(++p)->;y的结果是( ② ) 。
- 有如下定义:struct {int x; char *y;}tab[2]={{1,"ab"},{2,"cd"}}, *p=tab;则:表达式 *p->y的结果是( ① ) 。表达式 *(++p)->y的结果是( ② ) 。
- 有如下定义: struct { int x; char *y; }sa[2]={{1,"ab"},{2,"cd"}},*p=sa; 则:表达式 ++p->x 的值是 。
- 中国大学MOOC: 有如下定义: struct { int x; char *y; }sa[2]={{1,ab},{2,cd}},*p=sa; 则:表达式 ++p->x 的值是 。
内容
- 0
定义 struct{int n;<br/>char y[5];<br/>}tab[2]={{1,"ab"},{2,"cd"}}, <br/>*p=tab;<br/>则表达式:printf("%s\n",p->y);的结果为ab。
- 1
中国大学MOOC: 有如下定义: struct { int x; char *y; }sa[2]={{1,ab},{2,cd}},*p=sa; 则:表达式 (p+1)->x 的值是 。
- 2
有如下定义:struct{int x;int y;}s[2]={{1,2},{3,4}}, *p=s;则:表达式 ++p->;x的结果是( ① ) 。表达式(++p)->;x的结果是( ② ) 。
- 3
有如下定义: struct { int x; char *y; }sa[2]={{1,"ab"},{2,"cd"}},*p=sa; 则:语句:printf("%s",(++p)->y); 的输出是 。
- 4
以下程序的输出结果为()。#include "stdio.h"struct{int x;char *c;}st[2]={{1,"ab"},{2,"cd"}},*p=st;main(){printf("%c\t",*p->c);printf("%s\n",(++p)->c); }